Oxidation of cefazolin by potassium permanganate: Transformation products and plausible pathways. (April 2016) - Li, Liping; Wei, Dongbin; Wei, Guohua; Du, Yuguo
Abstract: Cefazolin was demonstrated to exert high reactivity toward permanganate (Mn(VII)), a common oxidant in water pre-oxidation treatment. In this study, five transformation products were found to be classified into three categories according to the contained characteristic functional groups: three (di-)sulfoxide products, one sulfone product and one di-ketone product. Products analyses showed that two kinds of reactions including oxidation of thioether and the cleavage of unsaturated CC double bond occurred during transformation of cefazolin by Mn(VII). Subsequently, the plausible transformation pathways under different pH conditions were proposed based on the identified products and chemical reaction principles. More importantly, the simulation with real surface water matrix indicated that the proposed transformation pathways of cefazolin could be replayed in real water treatment practices. Highlights: Di-ketone was formed via oxidation of CC double bond in cycloolefin with Mn(VII). Sulfoxide/sulfone was formed via oxidation of thioether in cefazolin with Mn(VII). Reaction pathways of cefazolin with Mn(VII) can replay in real surface water matrix. Sulfoxide and sulfone products with higher potential risk deserve more attention.